Corporate social irresponsibility : individual behaviors and organizational practices - Stachowicz-Stanusch, Agata; Amann, Wolfgang; Mangia, Gianluigi (Contemporary perspectives in corporate social performance and policy (Series), 2017)
In a modern world in which one can observe managerial and investors' behaviors characterized by high risk, short term orientation, moral hazard and speculation, there is a need to form a new ethical paradigm to drive a more ethical oriented education and a substantial change to norms regulating markets and business behavior to sensitize investors and financial practitioners, so that humanity can evolve in a sustainable way. Therefore the main question we are striving to answer throughout the book 'Organizational Social Irresponsibility: individual behaviors and organizational practices' is the following: Do individual behaviors influence organizational socially irresponsible practices?Each separate chapter aims to find an answer to the above question. The book is divided into three parts: first: 'The dark side of organizational behaviors', second: 'Individual skills and the workplace' and third: 'Organizational politics, practices and tools. This book is authored by a range of authors from all over the world. They provide us with several theoretical and practical contributions into the topic of organizational social irresponsibility and individual behavior, facing different aspects (e.g. workplace wellness, decision-making, diversity management). We hope it will be useful for both business and academia and it will help to shape reflective, socially responsible managers of the future.